Children's version of the systemic clinical outcome and routine evaluation (C‐SCORE): Exploring the psychometric qualities in the Portuguese context. Issue 4 (25th May 2022) - Vilaça, Margarida; Veloso, Bruna; Stratton, Peter; Relvas, Ana Paula
Abstract: Current literature presents a gap in family functioning assessment instruments directed to children. The Child Systemic Clinical Outcome and Routine Evaluation (C‐SCORE) is a self‐report instrument, based on the original SCORE‐15, that measures different aspects of family functioning from the child's perspective. This study aims to explore the psychometric qualities of the Portuguese version of C‐SCORE using a sample of 119 children, aged 8–11 years, recruited from public (state) schools located in North Portugal. Results showed good internal consistency for the total scale and were consistent with the original factorial structure. Correlation analyses using the Perception Scale of Parenting Communication – Children (COMPA‐C) provided support for convergent validity. This study represents the first psychometric evaluation of the C‐SCORE using a sample of Portuguese children, with exploratory results suggesting that this version presents acceptable psychometric qualities, and may be especially useful to assess family functioning from the child's view.